2018
DOI: 10.1155/2018/6471324
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Roof Harvested Rainwater in Australia

Abstract: To address concern regarding water sustainability, the Australian Federal Government and many state governments have implemented regulatory mechanisms and incentives to support households to purchase and install rainwater harvesting systems. This has led to an increase in rainwater harvesting in regional and urban Australia. This review examines the implementation of the regulatory mechanisms across Australia. In addition, the literature investigating the potential health consequences of rainwater consumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 88 publications
0
33
0
1
Order By: Relevance
“…This value is 0.015 mg/L, 0.005 mg/L, and 0.01 mg/L for Pb, Cd, and As, respectively. Ni does not have a MCL values, but according to Chubaka et al (2018), the health limit for Ni is 0.02 mg/L. Results have shown that Cd had the highest values at all sampling sites (Table 4), at MN and BH, the TP being 7 and 14 times higher than the reference value, respectively.…”
Section: Concentration Of Metal In Wet Deposition Recommended Upper Lmentioning
confidence: 91%
See 2 more Smart Citations
“…This value is 0.015 mg/L, 0.005 mg/L, and 0.01 mg/L for Pb, Cd, and As, respectively. Ni does not have a MCL values, but according to Chubaka et al (2018), the health limit for Ni is 0.02 mg/L. Results have shown that Cd had the highest values at all sampling sites (Table 4), at MN and BH, the TP being 7 and 14 times higher than the reference value, respectively.…”
Section: Concentration Of Metal In Wet Deposition Recommended Upper Lmentioning
confidence: 91%
“…Trace metals occur in many environmental matrices, and can be naturally found in the Earth's crust (Chubaka et al 2018). According to the World Health Organization (WHO) Pb, Cd, As, and Ni are classified as highly toxic to humans.…”
Section: Assessment Of Ecological Risks and Potential Effects Of Incrmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the Australian states (South Australia, Victoria, New South Wales, Queensland, Northern Territory and Australia Capital Territory), with the exception of Western Australia and Tasmania, have regulations/specifications for rainwater tank installation [12]. NSW Government introduced BASIX during 2004 [9].…”
Section: Rainwater Tank Policy In Various States Of Australiamentioning
confidence: 99%
“…The Building Sustainability Index (BASIX) [9] in New South Wales (NSW), minimum regulatory requirements for achieving a 6-star water and energy standard in Victoria [10], and Queensland Development Code MP4.2 [11] in Queensland are some of the examples for enforcing rainwater tank installations through regulatory means. Chubaka et al [12] have discussed in detail the regulations and specifications for rainwater tank installation in Australian states. However, to fully understand the effectiveness of such legislation, a comprehensive assessment protocol covering biophysical, economic, environmental and social aspects is required.…”
Section: Introductionmentioning
confidence: 99%